PENDAMPINGAN PEMBUATAN KARBOL SEREH PEMBERSIH LANTAI DI DESA BARABATU LABBAKKANG PANGKEP - Gusnawati, Gusnawati; Arman, Muhammad; Nurjannah, Nurjannah; Ramadhani, Uni; Dahlan, Magpirah (Universitas Mataram, 2024)
The majority of the residents of Barabatu village in Labbakkang District, Pangkep, are farmers. The farmers' income is heavily dependent on their harvests, which causes the village's economy to rely significantly on the harvest seasons. Therefore, additional income is needed to improve the welfare of Barabatu villagers. Citronella plants grow abundantly in the residents' yards, and there are productive citronella plantations developed by members of the religious study group, which have great potential for creating disinfectant products from citronella to support the local economy. Citronella has antimicrobial and antifungal properties, making it effective and safe for use as a floor cleaner. The aim of this community service program (PKM) is to enhance the creativity and productivity of Barabatu villagers. Furthermore, it is hoped that through this PKM activity, residents will acquire skills in making citronella disinfectant, which can be developed into a small and medium-sized enterprise (SME) to support their economy. In the production of disinfectant from citronella, the method used by the PKM team from FTI-UMI involves presenting materials on the ingredients and the process of making citronella disinfectant. This is followed by practical sessions involving farmer groups and the women of the religious study group. The final stage includes evaluating and monitoring the PKM activities conducted in Barabatu village. As a result of the PKM activities, the community, especially members of the religious study group, have become skilled in making citronella disinfectant. Additionally, they have gained knowledge about the benefits of natural ingredients available in their surroundings that can be used for disinfectant production. Following the training, the community is able to develop floor disinfectants with various aromas using essential oils from different types of plants found in Barabatu village. Consequently, the residents of Barabatu village can establish disinfectant production as an SME, providing additional income for the villagers. The PKM activities in Barabatu village have had a positive impact on the residents' economic lives through the guidance of the religious study group members. This activity encourages the community to increase their creativity and fosters an entrepreneurial spirit among the villagers of Barabatu.